Determination of Chemical Composition, Total Flavonoid Content, Total Phenolic Content and Antioxidant Capacity of Various Crude Extracts of Manihot esculenta Crantz Leaves - Mohammad Shaheen Khan; Samina Khan Yusufzai; Lawrance Kimin; Noor Adzianni Nabila Binti Jabi (2018)
In the present study, the leaves of Manihot esculenta Crantz were extracted by various organic solvents viz. hexane, chloroform, ethyl acetate and subjected to GC-MS analysis to determine their chemical composition and antioxidant activity by DPPH assay. The GC-MS analysis of hexane extract displayed squalene (10.25%), 9-octadecenoic acid (Z)-, methyl ester (9.01%), phytol (8.71%) and hexadecanoic acid, methyl ester (8.33%) as major compounds. The major compounds present in the chloroform extract were β-amyrin (12.70%), phytol (11.35%), 1,4-methanoazulen-9-ol, decahydro-1,5,5,8atetramethyl-,[1R- (1α,3aβ,4α,8aβ,9S*)]- (10.98%), 6β-Bicyclo[4.3.0]nonane, 5β-iodomethyl-1β-isopropenyl-4α,5α-dimethyl-, (9.40%) and humulane-1,6-dien-3-ol (8.53%). In ethyl acetate extract, squalene (16.39%), 9,11-dimethyltetracyclo [7.3.1.0(2.7).1(7.11)]tetradecane (12.01%) and humulane-1,6-dien-3-ol (9.58%) were reported as major compounds. The total phenolic content for hexane, chloroform and ethyl acetate was 5.35 ± 0.66 mg GAE/g, 7.52 ± 0.09 mg GAE/g and 13.47 ± 0.56 mg GAE/g, respectively. Whereas the total flavonoid content for hexane, chloroform and ethyl acetate was 0.89 ± 0.17 mg QE/g, 2.69 ± 0.09 mg QE/g and 6.66 ± 0.94 mg QE/g, respectively. The antioxidant activity of ethyl acetate extract (IC50 = 0.19 mg/mL) was higher than chloroform (IC50 = 1.39 mg/mL) and hexane extracts (IC50 = 1.74 mg/mL), with respect to the standard butylatedhydroxytoluene (BHT) (IC50 = 0.04 mg/mL).